Distribution and Discharge of Dissolved Methane in the Middle Okinawa Trough, East China Sea - Zhang, Xianrong; Sun, Zhilei; Wang, Libo; Zhang, Xilin; Zhai, Bin; Xu, Cuiling; Geng, Wei; Cao, Hong; Yin, Xijie; Wu, Nengyou (Frontiers in Earth Science, 2020)
Widespread seepage of methane from seafloor sediments on continental margins are released into seawater, a portion of which may escape to the atmosphere. To assess the water column distribution characteristics of methane and its input to the atmosphere, we investigated methane emissions from the shelf and west slope of the back-arc Okinawa Trough (OT), East China Sea. Our results showed a heterogeneity distribution of methane within the water column. The highest value, which was more than 10 times of the background concentration, occurred near a cold seep in the north of the study area which was discovered by a remotely operated underwater vehicle (ROV). Other sources of methane to the water column of the OT, besides cold seepage input, probably also include in situ aerobic methane production, advective transport from the continental shelf, and/or hydrothermal venting. Furthermore, the sea-to-air flux of methane throughout the study area was up to 116 μmol m–2d–1, noticeably higher than that in many other continental shelf waters and seep sites globally, indicating that this region is an active CH4 emission area. Our findings demonstrate that methane discharged from both cold seeps and hydrothermal vents have a significant influence on the methane cycle in the OT, providing a new insight for the methane budget of back-arc basins.